Field response in the near-horizon limit of near-extremal five-dimensional black holes - Giribet, Gaston Enrique (2023)
We study the scalar probe in the near-horizon region of near-extremal five-dimensional black holes and the problem of reattaching the asymptotic region. We consider the example of a Myers-Perry black hole with two independent angular momenta, for which the problem can be solved analytically in terms of the Riemann P-symbols and the confluent Heun special function. By prescribing leaking boundary conditions similar to those considered in the context of Kerr/conformal field theory correspondence, we implement the attachment of the asymptotically flat region, matching the solutions in the near-horizon Myers-Perry geometry with those in the far region. This provides us with a set of explicit expressions for the field response in the background of five-dimensional stationary black holes near extremality, which enables us to highlight qualitative differences with the analogous problem in four dimensions.